Analisis Spasial Respon Bendungan terhadap Model Peak Ground Acceleration (PGA) Berdasarkan Karakteristik Mikrotremor, Geologi Regional dan Amatan Instrumentasi pada Bendungan Sermo Kulonprogo - Nugroho Budi Wibowo; Arif Gunawan (Department of Physics, Sebelas Maret University, 2017)
This study is a comprehensive-descriptive analysis elaboration to seismic hazards on Sermo Dam, while in terms of microtremor characteristic (PGA model), its regional geology and observation of instrumentation on it. Sermo Dam is the only one water resources infrastructure which lies in The Yogyakarta Province at time of earthquake disaster happened on May 2006. Basic theories used in this case are HVSR methods, determining sediment thickness, and Kanai Method for Maximum Ground Acceleration, Then, based on these we can analyze characteristics of responsiveness damin the form of local spatial region focused by amplitude (A), dominance frequency (fo), time period (T), sediment thickness (H) and Peak Ground Acceleration (PGA) based on microtremor approarch with seismograph TDS 303S. Besides, by an analysis on regional geology that can be obtainable the characteristic of Sermo Dam foundation which lies on the Old Andesite (Kebo Butak) Formation. They are relatively robust when subjected to seismic vibration of middle class to below (less than 7 Richter scale on design). Also it has some declining periodic trends by main dam whereas there is still in the initial stage of design tolerance. The final result is zoning classification of damagepotential with: (1) region by PGA values of 0.04≤ a <0.15g which they are minor impact damage on their buildings; (2) region by PGA values of 0.15≤ a <0.34g which they are medium impact damage on their buildings. The damage level is comparable by inclining of filler material thickness at damsite.